Advances and Trends in Omics Technology Development - Dai, Xiaofeng; Shen, Li (Frontiers in Medicine, 2022)
The human history has witnessed the rapid development of technologies such as high-throughput sequencing and mass spectrometry that led to the concept of ‘omics’ and methodological advance in investigating the cellular system in a comprehensive and systematic way. Yet, the ever-growing types of molecules and regulatory mechanisms keep being discovered persistently transform our understandings on the cellular machinery. This renders cell omics seemingly, like the universe, expand with no limit and our goal towards the complete harness of the cellular system merely impossible. Therefore, it is imperative to review what has been done and is being done to predict what could be done towards the translation of omics information to disease control with minimal cell perturbation. With a focus on the ‘big four omics’, i.e., genomics, transcriptomics, proteomics, metabolomics, we delineate hierarchies of these omics together with their epitomics and interactomics, and review technologies developed for interrogation. We predict, among others, redoxomics as an emerging omics layer that views cell decision towards the physiological or pathological state as a fine-tuned redox balance.